The importance of anemia and health-related quality of life in the elderly - Wratsangka, Raditya; Putri, Rully Ayu Nirmalasari Haryadi (Universa Medicina, 2020)
Anemia is a global health problem with an extremely high prevalence and occurring in nearly 25% of the world population, particularly in the elderly group. Currently Indonesia is facing a rapid growth of the elderly population, with around 21 million elderly (8.2% of the total population), that is projected to increase to 33.7 million (11.8%) in the year 2025. Anemia in the elderly is frequently neglected, although the facts show that low hemoglobin concentration is an important marker of physiological decline and functional limitations. Although the factor of intrinsic aging may cause low hemoglobin concentration, anemia in the elderly is known to have a wide range w88ith regard to etiology, underlying disorders, andÂ  possible mechanisms, such that it should be clinically followed up. Whatever its causes or underlying pathophysiological, anemia in the elderly has been proven to play a role in their morbidity and mortality, and may decrease their quality of life, that comprises all aspects of physical, mental, and social health, known as health-related quality of life (HRQoL). The impact of anemia on HRQoL has been studied in various populations, and most studies report the presence of an association between HRQoL and anemia in elderly individuals, which on the subscale level is particularly associated with physical health. Early diagnosis of anemia is important to prevent aggravation of the condition, to retard the progress of the disease, and to improve the health-related quality of life (HRQoL) of the patient. Prior to determining the treatment plan, the primary diagnosis and the comorbidities, especially treatable disorders, had better be identified first. The available data show that the overall prognosis will improve for anemia in patients with well-managed and corrected chronic disorders.